Trinitas Visional: Trio Surgawi Ellen G. White dan Adventisme Kontemporer - Deky Hidnas Yan Nggadas; Meriwati Meriwati (JURNAL LUXNOS, 2025)
Ellen G. White is highly esteemed in Adventism as an infallible interpreter of Scripture. She is also famous for a concept she referred to as the "Heavenly Trio." This term is not merely a neologism, but rather an indication that its conceptual content is fundamentally different from the general and historical formulations of Trinitarianism. Nevertheless, the Seventh-day Adventist Church continues to identify itself as a Trinitarian Christian Church. Contemporary Adventist theologians also refer to Ellen's "Heavenly Trio" as a "Biblical Trinity." After thoroughly researching and analyzing her primary sources, we reject the label "Biblical Trinity" for Ellen's "Heavenly Trio," which we believe is more accurately described as a "Visional Trinity." We also reject the term "Trinitarian Christian" for Ellen's position, which has been passed down in contemporary Adventism. The concept of Ellen's "Heavenly Trio," which is labeled as a Biblical Trinitarian view in contemporary Adventism, should, in essence, be classified as a form of Monarchian Tritheism.